KARAKTERISASI FENOTIPIK UBI KAYU (Manihot esculenta Crantz) LOKAL SUMATERA BARAT - Nova Reskhi Firdaus; PK. Dewi Hayati; Yusniwati Yusniwati (Faculty of Agricultural Technology, University of Jember, 2016)
This research was conducted from October 2015 through March 2016 in four districts in West Sumatera. The aim of this research was to obtain initial information about the phenotypic variability of cassava accessions in West Sumatra. A survey was conducted in four centres of cassava production in West Sumatra : Koto Tangah, Padang; Batang Anai, Padang Pariaman; Pariaman Selatan, Pariaman; Tilatang Kamang, Agam. Phenotypic characterization was performed of leaves, stem, and tubers, as well as the chemical characterization of cassava tubers. The 15 cassava accessions showed narrow to wide phenotypic variability in leaf, stem and tuber characteristics. Cluster analysis based on qualitative and quantitative characteristics resulted in four groups of cassava with 50 % similarity. A similar result was found based on just quantitative characteristics, whereas using just qualitative characteristics resulted in just three groups.Keywords: Cassava, accessions, characterization, phenotypic, cluster